Pengaruh Cafe Atmosphere, Experiential Marketing Dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Cafe House Of Essentials Mojokerto - Evi Novita Sari; Hartono Hartono; M. Syamsul Hidayat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Business people in Indonesia, especially in Mojokerto, have a high demand for the cafe industry. The number of cafes that have sprung up resulted in business owners trying to win the competition. Each cafe experiences different updates and improvements in cafe atmosphere, experiential marketing, and product quality. In addition, this level of competition encourages cafes to compete with each other to get the best, which can have an impact on consumer satisfaction. This study aims to determine and analyze the effect of cafe atmosphere, experiential marketing, and product quality on customer satisfaction at Cafe House Of Essentias. This research is a research with quantitative methods. The population in this study are consumers who make purchases at Cafe House Of Essentias. The sample of this research was 125 respondents using accidental sampling technique. The data collection technique uses a questionnaire by distributing Google Forms to consumers. The data analysis technique uses the SPSS 25 program. The results of this study indicate that the cafe atmosphere variable has a positive and significant influence on customer satisfaction, experiential marketing has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction. And the consumer satisfaction variable is able to mediate the influence of the cafe atmosphere, experiential marketing, and product quality on customer satisfaction at Cafe House Of Essentials.